Prevalence and characterization of methicillin resistant staphylococcus spp. in surface water of Dhaka - Masnun, Adiba (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.